Young generation and sport : Promotion of regular physical activity in the Czech Republic - Vraný, Marcel (2022)
This thesis deals with promoting regular physical activity among the young generation, aged between 15 and 29 years old, in the Czech Republic. This thesis aims to find out what would motivate members of the young generation to regular physical activity. The thesis is divided into two parts. The first part deals with introducing the term physical activity, its importance and its connection with physical, mental and social health. The second part includes a quantitative questionnaire and the results of the analysis. These results suggested concrete recommendations on how to promote regular physical activity among the young generation.